PROBLEMS IN TRANSLATED ABSTRACT OF STUDENTS’ THESIS AT UNIVERSITAS BUNG HATTA - Fitrina Harmaini (Universitas Bung Hatta, 2022)
This study aims at analyzing problems identified in English-translated abstract of students’ theses. The problems are categorized into: grammatical problem and lexical problem. Due to the large number of population, proportionate stratified random sampling technique with 5 % margin of error was applied. The numbers of sample were 172 thesis abstracts. Thses written by students majoring in English were excluded. The problems were investigated by using text analysis. The analysis revealed that students had a lot of grammatical and lexical problems in their English –translated abstract. Based on the appearance of their translated abstracts, it is assumed that mother tounge interference affected them. REFERENCES Baker, Mona (1992) In Other Words. London and New York: Routledge. Catford, John C. (1980) A Linguistic Theory of Translation : An Essay in Applied Linguistics. London : Oxford University Press Cho, Jacee & Slabakova, Roumyana (2015) A feature-based contrastive approach to the L2 acquisition of specificity, Applied Linguistics. (1-23) Ciordia, Leticia Santamaria (2016) A contrastive and sociolinguistic approach to the translation of vulgarity from Spanish into English and Polish in the film Tie me up! Tie me down! (Pedro Aldomovar), Translation and Interpreting Studies. 11(2)(287-305). Hatim, Basil and Munday, Jeremy (2004) Translation. London & New York: Routledge Lubis, Syahron (2013) Collocation as source of translation unacceptability: Indonesian students’ experiences, International Journal of English Linguistics. 3(5)(20-28) doi: 10.5539/ ijel.v3n5p20 Munday, Jeremy (2008) Introducing Translation Studies: Theories and Applications (2nd ed.), London & New York: Routledge Nurasieta, Ajeng Febriani (2015) the Translation of Demonstrative References from English into Indonesian in Thesis Abstracts in Study Program of English Universitas Brawijaya. Repositori, 2(10). Diunduh dari: http://jimbastrafib.studentjournal.ub.ac.id/ Samdi, Mohsen, dkk (2011) Problems in the Translation of Legal Terms from Persian into Englsih. Language Society and Culture, (33)(pp.108-14). Diunduh dari: www.educ.utas. edu.au/users/tle/journal/ Sukirmiyadi, dkk (2014) A Study on the Quality of Abstract Translation of Dissertation from Indonesian into English. International Journal of Linguistics, 6(2)(pp.276-96). Diunduh dari: www.macrothink.org/ijl Ulrych, Margherita & Amanda Murphy (2008) Descriptive translation studies and the use of corpora: Investigating mediation universals. In Carol Taylor Torsello, Katherine Ackerley & Erik Castello (eds.), Corpora for university language teachers, pp. 141 - 66. Bern: Peter Lang. Williams, Jenny and Chesterman, Andrew (2002) The Map. UK: St. Jerome Publishing Wright, S (2002) From Academic Comparative Law to Legal Translation in Practice.